Lithium Phosphonate Functionalized Polymer Coating for High‐Energy Li[Ni0.8Co0.1Mn0.1]O2 with Superior Performance at Ambient and Elevated Temperatures. (16th July 2021) - Chen, Zhen; Nguyen, Huu‐Dat; Zarrabeitia, Maider; Liang, Hai‐Peng; Geiger, Dorin; Kim, Jae‐Kwang; Kaiser, Ute; Passerini, Stefano; Iojoiu, Cristina; Bresser, Dominic
Abstract: High‐energy Ni‐rich lithium transition metal oxides such as Li[Ni0.8 Co0.1 Mn0.1 ]O2 (NCM811 ) are appealing positive electrode materials for next‐generation lithium batteries. However, the high sensitivity toward moist air during storage and the high reactivity with common organic electrolytes, especially at elevated temperatures, are hindering their commercial use. Herein, an effective strategy is reported to overcome these issues by coating the NCM811 particles with a lithium phosphonate functionalized poly(aryl ether sulfone). The application of this coating allows for a substantial reduction of lithium‐based surface impurities (e.g., LiOH, Li2 CO3 ) and, generally, the suppression of detrimental side reactions upon both storage and cycling. As a result, the coated NCM811 ‐based cathodes reveal superior Coulombic efficiency and cycling stability at ambient and, particularly, at elevated temperatures up to 60 ° C (a temperature at which the non‐coated NCM811 electrodes rapidly fail) owing to the formation of a stable cathode electrolyte interphase with enhanced Li + transport kinetics and the well‐retained layered crystal structure. These results render the herein presented coating strategy generally applicable for high‐performance lithium battery cathodes. Abstract : Coating Li[Ni0.8 Co0.1 Mn0.1 ]O2 with a lithium phosphonate functionalized polymer enables the suppression of undesired reactions with moist air (i.e., H2 O and CO2 ) upon storage/processing, facilitates charge transfer, and enhances the thermal stability, thus achieving a substantially enhanced rate capability, Coulombic efficiency, and long‐term cycling stability – especially at elevated temperatures as high as 60 °C.